TRANSFORMASI DIGITAL MARKETING DAN BRAND IMAGE DALAM MENINGKATKAN PURCHASE INTENTION: STUDI EMPIRIS PADA KONSUMEN PRODUK KOSMETIK WILAYAH URBAN - Burhanudin; Zusrony, Edwin; Sumarlin, Tantik (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the role of digital marketing and brand image on consumer purchasing interest in cosmetic products in urban areas in Semarang, Central Java. This study uses a quantitative approach involving 60 respondents aged 18-50 years old and selected through a purposive sampling technique. The data analysis technique uses multiple linear regression and is processed using SmartPLS version 4.1.1.2. The research findings prove that digital marketing and brand image have a positive and significant impact partially on consumer purchasing interest in cosmetic products in Semarang. Digital marketing and brand image have a simultaneous impact on consumer purchasing interest in cosmetic products in Semarang. This finding emphasizes the importance of digital marketing and brand image in increasing consumer purchasing interest in cosmetic products in Semarang.